2017
DOI: 10.1093/femspd/ftx012
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli diseases in Latin America—a ‘One Health’ multidisciplinary approach

Abstract: The emergence and evolution of pathogenic Escherichia coli strains associated with animal and human infections continues being a topic of active investigation in recent years. Latin America has responded to this thread establishing the Latin American Coalition for Escherichia coli Research (LACER), a multidisciplinary group of scientists applying principles of the One Health initiative. LACER is integrating animal, human and environmental health for the mutual benefit of all, while reducing the impact of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…In our study, ETEC presented low prevalence and was only isolated from children without diarrhea, suggesting that this pathotype does not represent a relevant etiological agent for diarrhea in the indigenous Guarani population. The virulence genotype detected, codifying for both classes of enterotoxin, has been detected in ETEC isolates from non-indigenous children without diarrhea, which is in accordance with our findings [9] [11] [12]. ETEC clinical isolates frequently exhibit diverse adhesins capable of mediating the bacterial adherence with the surface of intestinal cells, contributing in this way to the full expression of the enteroinfection [9] [12].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study, ETEC presented low prevalence and was only isolated from children without diarrhea, suggesting that this pathotype does not represent a relevant etiological agent for diarrhea in the indigenous Guarani population. The virulence genotype detected, codifying for both classes of enterotoxin, has been detected in ETEC isolates from non-indigenous children without diarrhea, which is in accordance with our findings [9] [11] [12]. ETEC clinical isolates frequently exhibit diverse adhesins capable of mediating the bacterial adherence with the surface of intestinal cells, contributing in this way to the full expression of the enteroinfection [9] [12].…”
Section: Discussionsupporting
confidence: 88%
“…Phylogrouping assays classified the ETEC isolates as belonging to group A. These results are in accordance with previous findings, which revealed that phylogroup A is associated with clinical isolates of ETEC obtained from asymptomatic individuals, commensals of environmental origin or even of low virulence potential[9] [12][14] [15][37]. Our results from adherence assays revealed that the ETEC isolates were adherent, exhibiting the aggregative phenotype, typically observed in EAEC, and undefined patterns.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In this sense, virulence factors secreted by pathogens may also impair the correct placentation. STEC are foodborne bacteria that, once ingested, colonize the intestine and promote the production and absorption of Stx responsible for triggering cell death in target organs (Torres 2017). We propose that Stx may mediate EVT impairment leading to pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%